2014
DOI: 10.1212/wnl.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous splice mutation in CWF19L1 in a Turkish family with recessive ataxia syndrome

Abstract: Objective: To elucidate the genetic cause of a rare recessive ataxia presented by 2 siblings from a consanguineous Turkish family with a nonprogressive, congenital ataxia with mental retardation of unknown etiology.Methods: Whole-exome sequencing was combined with homozygosity mapping, linkage, and expression analysis to identify candidate genes, confirmed by Sanger sequencing. Reverse transcription-PCR and immunoblotting were used to determine the functional consequences of the gene variant. A zebrafish model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…3 The authors showed that knockdown of the homolog of CWF19L1 in zebrafish results in cerebellar and movement abnormalities and that the encoded protein C19L1 is expressed throughout the brain suggesting an important role for C19L1 in neural development. 3 Although the exact function of the C19L1 is still unknown, the nuclear localization in combination with a metallophosphatase domain, which is found in RNA lariat debranching enzymes, suggests a role in mRNA processing. 3 However, further studies are needed to determine the exact function of this protein and its role in brain development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The authors showed that knockdown of the homolog of CWF19L1 in zebrafish results in cerebellar and movement abnormalities and that the encoded protein C19L1 is expressed throughout the brain suggesting an important role for C19L1 in neural development. 3 Although the exact function of the C19L1 is still unknown, the nuclear localization in combination with a metallophosphatase domain, which is found in RNA lariat debranching enzymes, suggests a role in mRNA processing. 3 However, further studies are needed to determine the exact function of this protein and its role in brain development.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although the exact function of the C19L1 is still unknown, the nuclear localization in combination with a metallophosphatase domain, which is found in RNA lariat debranching enzymes, suggests a role in mRNA processing. 3 However, further studies are needed to determine the exact function of this protein and its role in brain development. Detailed functional characterization of C19L1 will provide more information on different causes of ARCA and possibly reveal novel candidates for the analysis of pathogenic variants in patients and/or targets for therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include five NTC core components: Cdc5, which plays an important role in pre-mRNA splicing by stabilizing the second-step spliceosome (60-62); Cwf7, which modulates interactions of Prp19 with other associated cofactors (63,64); Cwf2/Prp3, which helps link NTC to the catalytic center; Cwf1/Prp5, which contains a 7-bladed β-propeller; and Cwf15, which interacts with U5 snRNA, Prp5, and Spp42. In addition, we modeled four NTR components: Cwf5/Ecm2, which is involved in base pairing interactions of U2/U6 helix II (65); Cwf11, which is an ARM domain containing RNA helicase (49); Cwf14, which facilitates both steps of the splicing reaction (66); and Cwf19, Whose human ortholog is thought to be involved in the development of recessive ataxia syndrome (67). We also identified Prp17 and the prolyl isomerase Cyp1 in the EM density map.…”
Section: Protein Components In Ntc and Ntrmentioning
confidence: 99%
“…The affected patients present with ataxic gait, dysmetries, variable mental retardation, cerebellar abnormalities and dysmorphic facies with heterogeneous penetrance. To date few genes/loci have been associated to autosomal recessive forms of cerebellar ataxias: ATCAY [5], chromosome 20q11-q13 locus [6], VLDLR [7], ZNF592 [8], SPTBN2 [9], CWF19L1 [10], PMPCA [11]. Calmodulinbinding transcription activator 1 (CAMTA1) maps on chromosome 1p36, carries 23 exons and encodes 2 protein isoforms in mammalians.…”
Section: Introductionmentioning
confidence: 99%